2001
DOI: 10.1164/ajrccm.163.3.2004160
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone Inhibits But Does Not Reverse Allergen-Induced Structural Airway Changes

Abstract: Ethical and technical reasons limit the possibility of evaluating the effects of inhaled corticosteroids on structural changes in airways of humans with asthma. We therefore evaluated whether fluticasone propionate (FP) modifies airway remodeling, induced by repeated allergen exposure in rats. Sensitized BN rats were exposed to aerosolized ovalbumin (OA) for 2 wk. To assess the effect of FP on the development of or on established airway remodeling, animals were treated with aerosolized FP or placebo during all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 34 publications
3
92
1
1
Order By: Relevance
“…They observed that treatment initiated at the onset of allergen challenge was effective at preventing increases in airway wall laminin, but interestingly was not effective at preventing airway hyperresponsiveness. This observation that concomitant treatment with corticosteroids was able to markedly reduce an aspect of airway wall remodelling is consistent with previous observations in a rat model of chronic allergen challenge [4]. Interestingly, in that study, treatment was also effective at preventing airway hyperresponsiveness.…”
Section: Inmansupporting
confidence: 92%
See 1 more Smart Citation
“…They observed that treatment initiated at the onset of allergen challenge was effective at preventing increases in airway wall laminin, but interestingly was not effective at preventing airway hyperresponsiveness. This observation that concomitant treatment with corticosteroids was able to markedly reduce an aspect of airway wall remodelling is consistent with previous observations in a rat model of chronic allergen challenge [4]. Interestingly, in that study, treatment was also effective at preventing airway hyperresponsiveness.…”
Section: Inmansupporting
confidence: 92%
“…The results of the studies of CHRISTIE et al [3] and that of VANACKER et al [4], as well as previous observations that anti-leukotriene agents are capable of preventing allergeninduced airway wall structural changes [5], point to a potential new approach to asthma management. If, in fact, some aspects of airway wall remodelling are functionally important, then should treatment strategies be devised to prevent this development?…”
Section: Inmanmentioning
confidence: 84%
“…From day 14-28, rats were exposed to aerosolised 1% weight/volume OA (Grade III; Sigma Chemical Co.) for 30 min, every 2 days, as previously described [13]. Thirty minutes prior to each OA exposure, the different groups were treated with 0.1, 1 or 10 mg aerosolised FP (GlaxoSmithKline, Uxbridge, UK) (nebuliser concentration in 30 mL 0.1% ethanol/ phosphate buffered saline (PBS)) or placebo.…”
Section: Animals and Study Designmentioning
confidence: 99%
“…The authors have previously shown in the rat model of airway remodelling that an aerosol of 10 mg fluticasone propionate (FP) totally prevented peribronchial eosinophilic inflammation, GCH, epithelial cell proliferation and increased fibronectin (FN) deposition in the airway wall and partly inhibited the development of airway wall thickening [13]. This model provides the opportunity to compare the dose-response curve of FP on different histological aspects of allergen-induced airway changes.…”
mentioning
confidence: 99%
“…S'il est utilisé a posteriori, ce traitement est inefficace [31]. Comme nous l'avons vu, l'épaissis-sement de l'espace sous-épithélial est observé très tôt chez l'enfant.…”
Section: Les Thérapeutiques Actuelles Et Futuresunclassified